1997
DOI: 10.1073/pnas.94.16.8596
|View full text |Cite
|
Sign up to set email alerts
|

Anteroposterior neural tissue specification by activin-induced mesoderm

Abstract: The transforming growth factor ␤ superfamily member, activin, is able to induce mesodermal tissues in animal cap explants from Xenopus laevis blastula stage embryos. Activin can act like a morphogen of the dorsoventral axis in that lower doses induce more ventral, and higher doses more dorsal, tissue types. Activin has also previously been reported to induce neural tissues in animal caps. From cell mixing experiments it was inferred that this might be an indirect effect of induced mesoderm signaling to uninduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 62 publications
3
11
0
Order By: Relevance
“…Differences in the amounts and peaks of expression of other marker genes (chd, cer and Xbra) between the two species suggested that there are different mechanisms to define expression levels in a germ layer-(tissue or position) or genespecific manner between Xenopus laevis and Xenopus laevis. Our experiments also revealed that activin-treated animal cap explants of Xenopus tropicalis can differentiate into mesodermal and endodermal tissues in a dose-dependent manner, as reported previously for Xenopus laevis (Ariizumi et al, 1991, Green et al, 1997, Green et al, 1992. This result indicates that there are common mechanisms of tissue differentiation, which are conserved among species.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Differences in the amounts and peaks of expression of other marker genes (chd, cer and Xbra) between the two species suggested that there are different mechanisms to define expression levels in a germ layer-(tissue or position) or genespecific manner between Xenopus laevis and Xenopus laevis. Our experiments also revealed that activin-treated animal cap explants of Xenopus tropicalis can differentiate into mesodermal and endodermal tissues in a dose-dependent manner, as reported previously for Xenopus laevis (Ariizumi et al, 1991, Green et al, 1997, Green et al, 1992. This result indicates that there are common mechanisms of tissue differentiation, which are conserved among species.…”
Section: Discussionsupporting
confidence: 71%
“…This study demonstrated that animal cap cells dissected from late blastulae of Xenopus tropicalis have the same competence in response to activin as Xenopus laevis animal caps studied previously (Ariizumi et al, 1991, Green et al, 1997, Green et al, 1992. Organizer and mesoderm marker genes were expressed in the same temporal and dose-dependent pattern.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Green et al, demonstrated that the activin A-treated dissociated animal cap cells interact with untreated animal caps cells, resulting in induction of neural tissues (Green et al, 1997). We demonstrated that, when cells treated with activin A were mixed with untreated cells, the activin A-treated (1 ng/ml) cells concentrated in a central mass of the aggregates and they effectively formed notochord (Kuroda et al, 2002, Kuroda et al, 1999.…”
Section: Introductionmentioning
confidence: 82%